NOISE FILTERING AND DETECTING EDGE IMAGE IN NONLINEAR ANISOTROPIC DIFFUSION - Hà, Nguyễn Hải; Nhu, Phạm Trần (Vietnam Journal of Science and Technology, 2012)
SUMMARYNonlinear Anisotropic Diffusion (NAD) is a smoothing while edge preserving process, which itself depends on local properties of the image. In order to avoid blurring of edges, automated  problem  for detecting edge pixels also differentiate between edge noise is important in NAD method. The main contribution in this paper to introduce an active stopping-function instead of Perona-Malik’s stopping-function and Tukey’s stopping-function in NAD model. Numerical experimental results are demonstrated for comparing effective of these stopping-functions to image quality evaluation criteria.